Princípio da moralidade e restrições no acesso aos cargos públicos: um estudo a partir do recurso extraordinário 1.308.883 do STF - BARBOSA, Bruno Augusto da Costa (2023)
The present study addresses the application of the principle of morality as a basis for restricting access to public positions. Its overall objective was to discuss the restriction on access to public positions based on morality requirements, through the analysis of the Extraordinary Appeal (RE) 1.308.883/SP of the Brazilian Federal Supreme Court (STF), which deemed constitutional Municipal Law nº 5.849/2019 of the municipality of Valinhos/SP, which prohibits the appointment of individuals convicted under the Maria da Penha Law. The study conducted was exploratory in nature and consisted of a literature review through the analysis of legislation, case law, books, and scientific articles that address the principle of morality and access to public positions. The research revealed that the requirement of morality criteria for access to public positions has been manifested in various forms within the Brazilian legal system. However, even national doctrine faces difficulties in establishing a clear definition and determining the scope of the principle of morality. In this context, STF's case law has established some guidelines for imposing restrictions on individuals' access to public positions based on moral issues. Considering the aspects raised, the analysis of the prohibition on appointing individuals convicted under the Maria da Penha Law revealed a weakness in terms of conducting an incompatibility assessment. It states that there should be a relevance between the accusation and the position in question, so that the restrictions must be strictly related to the nature and duties of the functions to be performed. The study concludes that a more comprehensive legal analysis is necessary, taking into account the complexity of the debate and the individuality of each case, in order to avoid excessively restrictive, disproportionate, or unequal measures. Further studies are needed to seek objective solutions that reconcile the need to preserve the morality of Public Administration with the right to broad access to public positions.